Productos y servicios que otorgan las cooperativas de ahorro y crédito y su impacto socio económico en el cantón La Mana periodo 201-2012, Plan de capacitación. - Mera Santana, Hiter Francisco (2013)
This thesis entitled, "Products and services that provide the Credit Unions and its socioeconomic impact in Canton La Maná period 2011-2012" evaluates theeconomic impact involved in cooperative services by unions credit in Canton LaManá. The need to propose innovative alternatives that meet the satisfaction of needs of the population, the problem arises of how products and services that provide thesavings and credit cooperatives affect the socioeconomic development of thepartners? In order to elucidate the problem arises research main objective Toevaluate the products and services that provide the savings and credit cooperatives and their impact on the socio-economic development of its partnersin the Mana Canton 2011-2012, The general hypothesis of departure is thefollowing, "The products and services that provide the credit unions are not adequate to achieve a high socio-economic development of the partners in theCanton La Maná." Scientific theory is grounded in the development of the theoretical framework of each variable depending on the assumptions, concepts defined on thecooperative, social and economic impact, and analyzes the products and services that provide the credit unions. Note that for the realization of the research used the following methods, theinductive allowed to observe the reality on the products and services that providecooperatives, the deductive method of testing hypotheses, the qualitative methodwhich leads to further specific cases in research and analytical method based onthe explanation of the information obtained with the above methods. We used thesurvey technique to extract and verify information obtained from citizens of CantonLa Maná...................................................................